Integrative Role of the SALL4 Gene: From Thalidomide Embryopathy to Genetic Defects of the Upper Limb, Internal Organs, Cerebral Midline, and Pituitary - Kodytková, Aneta; Dušátková, Petra; Amaratunga, Shenali Anne; Plachý, Lukáš; Průhová, Štěpánka; Lebl, Jan (Hormone research in paediatrics, 2024)
BACKGROUND: The thalidomide disaster resulted in tremendous congenital malformations in more than 10,000 children in the late 1950s and early 1960s. SUMMARY: Although numerous putative mechanisms were proposed to explain thalidomide teratogenicity, it was confirmed only recently that thalidomide, rather its derivative 5-hydroxythalidomide (5HT) in a complex with the cereblon protein, interferes with early embryonic transcriptional regulation. 5HT induces selective degradation of SALL4, a principal transcriptional factor of early embryogenesis. Genetic syndromes caused by pathogenic variants of the SALL4 gene phenocopy thalidomide embryopathy with congenital malformations ranging from phocomelia, reduced radial ray, to defects of the heart, kidneys, ear, eye, and possibly cerebral midline and pituitary. SALL4 interacts with TBX5 and a handful of other transcriptional regulators and downregulates the Sonic hedgehog signaling pathway. Cranial midline defects, microcephaly, and short stature due to growth hormone deficiency have been occasionally reported in children carrying SALL4 pathogenic variants associated with generalized stunting of growth rather than just the loss of height attributable to the shortening of leg bones in many children with thalidomide embryopathy. KEY MESSAGES: Thus, SALL4 joins the candidate gene list for monogenic syndromic pituitary insufficiency. In this review, we summarize the journey from the thalidomide disaster through the functions of the SALL4 gene to its link to the hormonal regulation of growth.
Keywords: Thalidomide; nemoci plodu; Upper Extremity; lidé; proteiny hedgehog; Fetal Diseases; Limb development; Pituitary development; mnohočetné abnormality; SALL4; Transcription Factors; Humans; Embryogenesis; horní končetina; Hedgehog Proteins; Abnormalities, Multiple; thalidomid; transkripční faktory